Recurrence of leprosy cases in a highly endemic area in Pará State, Brazil - Melo, Suenny Leal (2020)
It is considered as a case of leprosy relapse, the individual who, after having been discharged for healing, has presented clinical signs of disease activity. In order to know the occurrence of relapse, clinical and epidemiological factors in patients in a hyperendemic region, a survey was conducted which methods comprise an epidemiological cross-sectional descriptive study from January 2007 to December 2008, with data provided by Specialized Reference Center (Unidade de Referência Especializada - URE) in leprosy Dr. Marcello Candia, in Pará State, Brazil. The results of the study revealed that 96.3% of 27 patients belonged to the multibacillary classification, predominantly male (74.1%), with the age group from 29 to 42 years old (44.4%), most came from Belém metropolitan region (70.4%). The clinical manifestation characterized by new lesions (81.5%), with time of appearance between five and ten years (55.6%). The diagnosis used clinical and bacteriological index assessment (63%), of these 40.7% were smear between 4-6 +. The degree of disability in 44.4% was not recorded at the beginning of treatment. The cases of leprosy diagnosed and treated at URE Dr. Marcello Candia, mostly, met the criteria established by Brazilian Ministry of Health. The degree of disability of some patients did not show the result in this evaluation, which it is very important to prevent disabilities. The simplified dermatological assessment recommended by Ministry of Health should be reinforced in its importance in all services that have leprosy patients, since it is essential for the early diagnosis of neurological damage.